MLA 31-93 - Economic Analysis Of The Minerals Potential Of The West Mojave Management Area, Including The Desert Tortoise Priority Habitat, California ? Executive Summary ? Introduction (The National Institute for Occupational Safety and Health (NIOSH), 1993)
This U.S. Bureau of Mines (USBM) report conveys the results of an economic analysis of minerals in the West Mojave Management Area (WMMA), including the Desert Tortoise Priority Habitat (DTPH), a proposed special land management area. Undiscovered mineral resources were estimated for the entire WMMA, which totals 8.7 million acres. Known mineral resources were studied for the DTPH, which is an area of 1.2 million acres contained within the WMMA. Federal lands within the WMMA are managed by the Bureau of Land Management (BLM). The WMMA includes Federal, State, and private lands in the western portion of San Bernardino County and the eastern portion of Kern County. The center of the study area is 20 miles northwest of Barstow, California (Figures 1 and 2).